47 Retrospective analysis of the impact of full vs culprit only revascularisation in octogenarians with multi-vessel coronary artery disease. (4th June 2021) - Buttinger, Nicolas; Smith, Jonathan; de Belder, Adam
Abstract : Objectives: The aim of this study was to evaluate all-cause mortality in patients aged greater than 80 years old with multi-vessel (MV) coronary artery disease (CAD) presenting with an acute ST segment elevation myocardial infarction (STEMI) and the impact of culprit only (CORV) versus full revascularisation (FRV). Background: Current European Society of Cardiology (ESC) guidelines recommend FRV either during the index procedure or as a staged approach in patients presenting with STEMIs and found to have MV CAD. A recent meta-analysis demonstrated a 31% relative risk reduction in cardiovascular mortality in patients undergoing FRV. The average age of patients in the trials that have directed these guidelines is 61-65 and therefore their applicability to the elderly is questionable. Methods: This is a retrospective cohort study of patients presenting with a STEMI to the Royal Sussex County Hospital between January 2009 and December 2019. Groups were defined as those less than or greater than 80 years old and subdivided into those with single vessel (SV) or MV CAD. Group baseline characteristics were compared and the time to all-cause mortality from index procedure was assessed for each group. Logrank tests / cox-regression models were used for survival analysis and chi-squared tests for categorical data. Significance level = < 0.05. Results: 2809 eligible patients were identified during the study period. In those less than 80 years old (2418 patients) 1751 patients had SV CAD and 647 (26.8%) had MV CAD. Of those with MV CAD, 81 (12.5%) underwent FRV. In patients greater than 80 years old (391 patients) 247 patients had SV CAD and 144 (36.8%) had MV CAD of which 19 (13.2%) had FRV. Patients greater than 80 years old were significantly more likely to have MV CAD compared with patients less than 80 years old (p<0.0001). There was no significant difference between the two groups in the number of patients with MV CAD undergoing FRV (p=0.78). Patients less than 80 with MV CAD had a significantly higher mortality rate than those with SV CAD (HR 1.47 [95% CI 1.13-1.91], p=0.004). ( Figure 1B ) . Whereas in patients greater than 80 years old there was no significant difference in mortality rates between those with and without MV CAD (HR 1.34 [95% CI 0.97-1.85], p=0.07). ( Figure 1A ) . There was also no significant difference in mortality in patients with MV CAD greater than 80 years old undergoing CORV versus FRV (p=0.19). ( Figure 2 ) . Conclusions: The results show there is a mortality difference in patients with MV versus SV CAD in patients less than 80 years old, which is not seen in patients greater than 80 years old. There also does not appear to be a mortality benefit in FRV compared with CORV in the elderly. While a reduction in cardiovascular mortality with FRV has been demonstrated in a recent meta-analysis these results indicate that this benefit may be tempered in elderly patients. This is a single centre study with relatively small numbers, especially in those greater than 80 years old undergoing FRV. Given the uncertainty around FRV in the elderly, there remains a need for a randomised control trial to evaluate this question. Conflict of Interest: None